Adjuvant anticholinergic therapy for the prevention of akathisia in patients with primary headache in the emergency department: A systematic review. (1st September 2022) - Meyer, Jillian; Kirkland, Scott W.; Campbell, Sandra; Villa‐Roel, Cristina; Rowe, Brian H.
Abstract: Objectives: Adjunct therapy with anticholinergic agents has been proposed to reduce the incidence of extrapyramidal side effects such as akathisia following treatment with neuroleptics or metoclopramide. This systematic review assessed the effectiveness of anticholinergic agents to prevent neuroleptic or metoclopramide‐induced akathisia in patients presenting to the emergency department (ED) with benign headache. Methods: Eight electronic databases and the gray literature were searched to identify randomized controlled trials involving adult patients presenting to the ED with primary headache treated with neuroleptic or metoclopramide. Study selection, data extraction, and quality assessment were completed by two independent reviewers. Individual or pooled meta‐analysis of dichotomous outcomes were calculated as relative risks (RRs) with 95% confidence intervals (CIs) using a random‐effects model. Heterogeneity was assessed using the I 2 statistic. Results: A total of 1032 studies were screened, of which two studies were included in the review. Both studies provided patients with diphenhydramine following treatment with neuroleptics or metoclopramide. Treatment with diphenhydramine did not reduce the incidence of akathisia compared to treatment with placebo (RR 0.83, 95% CI 0.43–1.61, I 2 = 0%). The impact of diphenhydramine on pain relief, need for rescue medications, and relief of other extrapyramidal side effects was reported in one of the two studies, with no significant differences noted in any outcomes compared to patients treated with placebo. Conclusion: This review found insufficient evidence to recommend the use of diphenhydramine as an adjunct therapy to prevent akathisia in ED patients treated with neuroleptics or metoclopramide for primary headache. This finding relies on the results of two small randomized controlled trials with incomplete outcome reporting. Additional high‐quality studies are needed to better understand the clinical efficacy of agents with anticholinergic properties in the ED management of patients with primary headaches.